Building Sustainable Cancer Control Capacity and Infrastructure in Developing Countries - Burton, Professor Robert (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45478023/Building-Sustainable-Cancer-Control-Capacity-and-Infrastructure-in-Developing-Countries